Transport and Logistics and their Influence on Export Costs - Heda Hansenova; Vaclav Cempirek; Petr Novak (Communications - Scientific letters of the University of Zilina, 2016)
The paper deals with the role of transport and logistics as they relate to exports. We searched for the impact of transport and logistics on exports using transaction dynamics as described by Coase and Williamson. We deal with the costs of exchange using international sales contracts where the traditional calculation structure, based primarily on costs of delivery is extended with transaction costs. Furthermore, we measure the impact of such adjusted costs of exchange on the added value using Porter’s methods and determine which costs have the nature of investment. Finally, the effect of resource implementation into information and communication technologies and the related changes in transport and logistics are presented (in the paper).